Book Reviews. - Cull, Nicholas J.; Jarvie, Ian; Gomery, Douglas; Scott, Ian; Man, Randolph; Cole, Robert; Chapman, James; Voeltz, Richard A.; Kobland, Clifford; Nelson, Michael (Historical Journal of Film, Radio & Television, 2002)
Reviews several books on mass media. 'Mass Culture and National Traditions: The BBC and American Broadcasting, 1922–1954,' by Valeria Camporesi; 'Hollywood's Film Wars with France: Film-Trade Diplomacy and the Emergence of the French Film Quota Policy,' by Jens Ulff-Mφller; 'Sure Seaters: The Emergence of Art House Cinema,' by Barbara Wilinsky.